Profile of cognitive impairment in dementia associated with Parkinson's disease compared with Alzheimer's disease. Issue 10 (7th February 2007) - Bronnick, Kolbjorn; Emre, Murat; Lane, Roger; Tekin, Sibel; Aarsland, Dag
Abstract : Objective: To compare the profile of cognitive impairment in Alzheimer's disease (AD) with dementia associated with Parkinson's disease (PDD). Methods: Neuropsychological assessment was performed in 488 patients with PDD and 488 patients with AD using the Mini-Mental State Examination (MMSE) and the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). Logistic regression analysis was used to investigate whether the diagnosis could be accurately predicted from the cognitive profile. Additionally, the cognitive profiles were compared with a normative group using standardised effect sizes (Cohen's d). Results: Diagnosis was predicted from the cognitive profile, with an overall accuracy of 74.7%. Poor performance of the AD patients on the orientation test in ADAS-cog best discriminated between the groups, followed by poor performance of the PDD patients on the attentional task in MMSE. Both groups showed memory impairment, AD patients performing worse than PDD patients. Conclusion: The cognitive profile in PDD differs significantly from that in AD. Performance on tests of orientation and attention are best in differentiating the groups.